Who benefits from autonomous learning? (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article aims to investigate concepts of autonomous learning and its significance in contemporary education and professional development. In the era  of rapid technological advancement with global demand for lifelong learning, the ability to direct one`s own learning is more essential than ever. Autonomous learning helps learners to establish their own goals, select resources and think carefully about their progress, encouraging them for personal and professional growth. Traditionally, autonomous learning is associated with higher education, can provide benefits for a broad range of people including students, professionals and lifelong learners.